ANALYSIS OF 45,507 SURGICAL TREATMENT OF DISTAL TIBIA AND MALLEOLAR FRACTURES OVER 14 YEARS - DOV LAGUS ROSEMBERG; NELSON WOLOSKER; MARCELO FIORELLI ALEXANDRINO SILVA; TANIA SZEJNFELD MANN; VINCENZO GIORDANO; ALEXANDRE LEME GODOY-SANTOS (Acta Ortopédica Brasileira, 2023)
ABSTRACT The distal leg joint fractures are among the most common fractures in humans across all age groups, and 50% of them require surgical treatment. Few studies discuss the epidemiology and costs of this fracture in the global and national literature. Objective: To evaluate the annual incidence and reimbursement value of distal leg joint fractures requiring surgical treatment from 2008 to 2021. Methods: A retrospective study was conducted to analyze the complex structured data of high volume and high variability (Big Data), publicly available on the TabNet platform (DATASUS), via software with artificial intelligence. Data from 2008 to 2021 on surgical treatment for malleolar fracture, distal tibia fracture, and isolated fibula fracture were analyzed. Results: From 2008 to 2021, there was an average incidence of 28.8 fractures/105 inhabitants per year, representing 14.62% of all fractures. The total amount paid for hospitalizations due to these fractures was R$ 34,218,014.62 over these 14 years. Conclusion: The incidence of distal leg joint fractures follows the pattern of those recorded in other countries. The adjustment of reimbursement over the years was lower than the accumulated inflation. Level of Evidence II, Economic and Decision Analyses - Developing an Economic or Decision Model.